Politeness Strategy of Former British Prime Minister Liz Truss at the Prime Minister's Questions sessions YouTube UK Parliamentt - Eka Maharani Setiawan; Rejeki, Sari; Sari’at Kurniati, Nur Utami (Edu-Ling: Journal of English Education and Linguistics, 2024)
This research aims to analyze language politeness strategies used by former British Prime Minister Liz Truss in the Prime Minister's Questions session uploaded by the UK Parliament YouTube account in 2022 according to the theory of Brown and Levinson (1987). The method used in this research is descriptive qualitative. The results of the analysis show that negative politeness strategies were most often applied by former British Prime Minister Liz Truss during the Prime Minister's Questions session. In the analysis of 30 data, it was discovered that Liz Truss used the most negative politeness strategies (36%) in Prime Minister's Questions. The goal is to maintain a negative face and avoid open conflict. With this strategy, Liz Truss conveys messages subtly, minimizes the risk of conflict, and maintains social relations with interlocutor.